Re-using manuscripts in late Medieval England repairing, recycling, sharing - Ryley, Hannah 1990- (York manuscript and early print studies, 2022)
A fresh appraisal of late medieval manuscript culture in England, examining the ways in which people sustained older books, exploring the practices and processes by which manuscripts were crafted, mended, protected, marked, gifted and shared